Long-Term Follow-Up of Ultrasound-Guided Glossopharyngeal Nerve Block Treatment for Glossopharyngeal Neuralgia: A Retrospective Clinical Study of 43 Cases [Letter] - Xing C; Cheng S (Journal of Pain Research)
Chuyun Xing,1 Shizhou Cheng2 1Department of Pain Management, The First Affiliated Hospital of Yangtze University, Jingzhou, Hubei Province, 434000,People’s Republic of China; 2Department of Ophthalmology, The First Affiliated Hospital of Yangtze University, Jingzhou, Hubei Province, 434000,People’s Republic of ChinaCorrespondence: Shizhou Cheng, Email shizhou_Cheng@163.com